ANALISIS PENGENDALIAN KUALITAS PAVING MENGGUNAKAN METODE SIX SIGMA PADA CV MTU - I Gede Ekasatmika Prabaswara,Mia Juliana, Bryan Estavan Imanuel Sitanggang (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2023)
This study aims to determine the quality of brick model paving products at CV MTU with the six sigma method and the causes of defects in paving products at CV MTU. The data used in this study are primary data and secondary data related to the production process of paving brick models sourced from the company and from the literature. Primary data obtained through direct observation and interviews with parties involved in the production process. Secondary data was obtained from documents and reports related to the paving production process. The production data used is data for six months of production from July 2022 to December 2022. This research uses the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The results of this study indicate that the level of quality control at CV